2004
DOI: 10.1084/jem.20030680
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of Sphingosine-1–Phosphate Receptors by FcεRI Triggering Is Required for Normal Mast Cell Degranulation and Chemotaxis

Abstract: Mast cells secrete various substances that initiate and perpetuate allergic responses. Cross-linking of the high-affinity receptor for IgE (FcɛRI) in RBL-2H3 and bone marrow–derived mast cells activates sphingosine kinase (SphK), which leads to generation and secretion of the potent sphingolipid mediator, sphingosine-1–phosphate (S1P). In turn, S1P activates its receptors S1P1 and S1P2 that are present in mast cells. Moreover, inhibition of SphK blocks FcɛRI-mediated internalization of these receptors and mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
422
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 306 publications
(448 citation statements)
references
References 46 publications
(98 reference statements)
22
422
3
1
Order By: Relevance
“…4 In agreement, FTY720-phosphate, an agonist of all S1P receptors except S1P 2 , did not induce degranulation. 19 Moreover, quantitative real-time PCR (QPCR) revealed that like rodent MCs, LAD2 cells as well as cord blood-derived human MCs and human skin MCs express similar levels of S1P 1 and S1P 2 , but do not express S1P 3-5 receptors (data not shown).…”
Section: S1p Stimulates Degranulation and Cytokine And Chemokines Relsupporting
confidence: 56%
See 4 more Smart Citations
“…4 In agreement, FTY720-phosphate, an agonist of all S1P receptors except S1P 2 , did not induce degranulation. 19 Moreover, quantitative real-time PCR (QPCR) revealed that like rodent MCs, LAD2 cells as well as cord blood-derived human MCs and human skin MCs express similar levels of S1P 1 and S1P 2 , but do not express S1P 3-5 receptors (data not shown).…”
Section: S1p Stimulates Degranulation and Cytokine And Chemokines Relsupporting
confidence: 56%
“…Secretion of granules was determined by measuring the release of the granule marker ␤-hexosaminidase with a colorimetric assay in which the production of p-nitrophenol from p-nitrophenyl-N-acetyl-␤-D-glucosaminide is measured. 4 Values are expressed as the percentage of total cellular ␤-hexosaminidase released into the medium. Chemotaxis was measured in transwells (Costar, Cambridge, MA) with 8-m pore size.…”
Section: Degranulation and Chemotaxismentioning
confidence: 99%
See 3 more Smart Citations